High levels of Trypanosoma cruzi DNA determined by qPCR and infectiousness to Triatoma infestans support dogs and cats are major sources of parasites for domestic transmission - Enriquez, G F (2014)
Fil: Enriquez, G.F. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Laboratorio de Ecoepidemiología; Argentina.